An effective and economic approach for the eradication of Helicobacter Pylori:omeprazole and two antibiotic combination - Abdurrahman KADAYIFÇI; Halis ŞİMŞEK; Gonca TATAR (Turkish Journal of Gastroenterology, 2019)
-